In the Shadow of Legal Imperialism: The Supremacy of EU Law Over the Member States - Metzinger, Péter (The Policies of the European Union from a Central European Perspective, 2022)
The primacy of EU law over the domestic law of the Member States is a matter of course. Nonetheless, the precise boundaries of EU law are often disputed between the Member States and the EU: while the Court of Justice of the EU draws those boundaries pursuant to the autonomy (sovereignty) of the EU legal order (i.e., from the inside), the national constitutional courts define the same boundaries pursuant to their own national constitutions (i.e., from the outside). The parallel jurisdiction of the Court of Justice and of the constitutional courts has exposed the tensions between the rule of law and democracy, and between the legal sovereignty of the European legal order and the popular sovereignty of European nations. Insofar as these tensions are resolved only according to the rule of law, without democratic processes, legal imperialism will impose itself.Keywords: conflict of jurisdictions, constitutional identity, democracy, European legal order, pluralism,primacy, rule of law, sovereignty, supremacy, ultra vires.